BITCOIN DIGITAL CURRENCY IN THE INTERNATIONAL LAW FRAME IN TERMS OF REGULATION AND REFORM - Khalid Muayad Younus (Scholar Express Journals, 2021)
This study assumes that the economy is a major driver of social change. The presence of the bitcoin phenomenon, which is a means of trade that does not recognize governmental restrictions, demonstrates the impact of globalization on the economic sector. In many countries and areas, this has been a source of concern for both internet users and regulators. More intriguingly, due to their large population, countries have emerged as one of the most important markets for bitcoin users. The challenge stated in this research is the impetus for bitcoin regulation in international law reform. The method employed in this study is sociolegal research. There are two aspects of research in the socio legal research approach: legal aspects of research, which refer to the object of research in the form of law in the sense of norms of law, and socio-research aspects, which use the methods and theories of social science about law to assist in conducting analysis. The paradigm employed in this study is post positivism with legislative ontology. in terms of currency and law pertaining to bank countries Because technological breakthroughs such as bitcoin cannot be avoided, the country's government must adapt to this disruptive technology without jeopardizing international interests. In reaction to the introduction of such technical products, legislation is deemed flawed because it does not entirely guarantee protection for people as well as certainty for bitcoin users. It is expected that the implementation of legal reforms through legal political responsiveness in formulating the law, which was originally capable of adapting to the conditions and needs of today's society, will improve the value and functionality of law in terms of certainty, as an imperative norm with feasible and measurable regulation, and coercive capability
Keywords: Regulation; bitcoin; economy; globalization impact